Comparative Transcriptomic and Proteomic Analysis of Exopalaemon carinicauda in Response to Alkalinity Stress - Qin, Zhen; Ge, Qianqian; Wang, Jiajia; Li, Mingdong; Liu, Ping; Li, Jian; Li, Jitao (Frontiers in Marine Science, 2021)
Saline-alkaline waters are stressful environments where most aquatic animals can’t survive normally, and alkalinity is one of the key limited environmental factors. Due to strong adaptability to environment，the ridgetail white prawn Exopalaemon carinicauda is a potential good species suitable for large-scale culture in saline-alkaline waters. Exploring its alkaline adaptability mechanism will help to guide more marine crustaceans to saline-alkaline culture. In this study, an integrative analysis of the gill-specific transcriptome and proteome at 0 h, 12 h and 36 h after alkalinity stress was performed to identify important regulators and pathways involved in alkalinity adaption of E. carinicauda. A total of 3, 157 differentially expressed genes (DEGs) and 443 differentially expressed proteins (DEPs) were identified at 12 h and 36 h compared with 0 h. Base on the transcriptome analysis, the GO enriched terms were mainly related to ion transport, including “calcium-transporting ATPase activity”, “ATPase coupled ion transmembrane transporter activity”, “divalent inorganic cation transmembrane transporter activity” etc., and the KEGG pathways mainly refer to the processes of endocrine system at both 0 h, 12 h and 36 h. Based on the proteomic analysis, KEGG pathways related to lipolysis and amino acids metabolism were significantly enriched at 12 h, and carbohydrate metabolism and immune system were significantly enriched at 36 h. There were significantly up-regulated expressions of ion transport related genes including aquaporin, carbonic anhydrase, ammonium transporter Rh type A-like, Na+/H+-exchanger etc., as well as ion transport proteins including V-type proton ATPase 116 kDa subunit a-like isoform X1, sodium-potassium ATPase beta, vesicle associated membrane protein, etc. after alkalinity exposure, which indicating their important roles in response to alkalinity stress. The results of integrated analysis between proteome and transcriptome showed that up-regulated DEG/DEP (aldehyde dehydrogenase) was significantly enriched at 12 h and the up-regulated DEG/DEP (peptidylglycine alpha) was significantly enriched at 36 h, suggesting the two molecules may be critical in response to alkalinity change. This study reveals the first time-course, gill-specific, combined transcriptomic and proteomic profiling associated with alkalinity adaption of E. carinicauda and provides new insights into the mechanisms underlying the molecular response to alkalinity stress in shrimp.